2014
DOI: 10.1021/ja5081647
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite Formation via Kinetic Intermediates through Low-Temperature Solid-State Metathesis

Abstract: The preparation of materials with limited phase stabilities yet high kinetic activation barriers is challenging. Knowledge of their possible formation pathways aids in addressing these challenges. Metathesis reactions present an approach to circumvent these barriers; however, solid-state metathesis reactions are often too rapid from extensive self-heating to understand the reaction. The stoichiometric reaction of MCl2 salts (M = Mn, Fe, Co, Ni, Cu, Zn) with Na2S2 enables the formation of pyrite (FeS2), CoS2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…[56][57][58] Lower temperature (500 K to 650 K) metathesis reactions have allowed some pyrites to synthesized in just days by circumventing kinetic barriers. 59,60 Butala et al demonstrated microwave preparation of Fe 1−x Co x S 2 and CuTi 2 S 4 , accelerating reaction times to less than 40 minutes. 61 The microwave electromagnetic field interacts strongly with the transition metal, selectively heating the metal powder and allowing the reaction to occur rapidly at metal sites before significant sublimation of the chalcogen.…”
Section: Transition Metal Chalcogenidesmentioning
confidence: 99%
“…[56][57][58] Lower temperature (500 K to 650 K) metathesis reactions have allowed some pyrites to synthesized in just days by circumventing kinetic barriers. 59,60 Butala et al demonstrated microwave preparation of Fe 1−x Co x S 2 and CuTi 2 S 4 , accelerating reaction times to less than 40 minutes. 61 The microwave electromagnetic field interacts strongly with the transition metal, selectively heating the metal powder and allowing the reaction to occur rapidly at metal sites before significant sublimation of the chalcogen.…”
Section: Transition Metal Chalcogenidesmentioning
confidence: 99%
“…Martinolich et al . reported the salt‐exchange metathesis reaction approach for the synthesis of high purity pyrite at low temperature 350 °C through intermediate pyrite phases.…”
Section: Pyrite Thin Films For Photovoltaicsmentioning
confidence: 99%
“…Several GEFs (e.g., EPAC, C3G, PDZ-GEFs, CalDAGs, and RapGEF6) have been indicated as activating Rap1 for GTP forms in different cells [ 12 , 27 , 28 , 29 , 30 , 31 ]. Two of them, EPAC and RapGEF6, are involved in male germ cells [ 13 , 30 ]. EPAC (exchange protein directly activated by cAMP) is colocalized with Rap1 within murine spermatocytes and round spermatids.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of another GEF, RapGEF6, results in male infertility, and accounts for reduced testis size as well as reduced sperm count and motility. Moreover, the knockout also produces high percentages of morphologically abnormal sperm [ 30 ]. Several GAPs are involved in the inactivation of Rap1 in non-germ cell lines (e.g., Rap1-GAP1, Rap1-GAP2, Spa1, and SPAR1,2,3) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%